IMPLEMENTASI MANAJEMEN STRATEGIK SEBAGAI UPAYA PENINGKATAN MUTU PENDIDIKAN: STUDI LITERATUR TERHADAP PRAKTIK DI SEKOLAH - Muhammad Hasan Basari; Putri Solekha; Irma Indriani Aisyah; Dwi Kartika Septiawati (JIP: Jurnal Ilmu Pendidikan, 2025)
This study aims to examine the implementation of strategic management as an effort to improve educational quality through a literature review of practices applied in various schools. In the educational context, strategic management is understood as a systematic process encompassing planning, implementation, evaluation, and control of strategies to achieve effective and sustainable educational objectives. This literature study analyzes previous research findings, scholarly articles, and relevant educational policy reports focusing on school quality improvement. The findings reveal that the implementation of strategic management significantly contributes to enhancing educational quality, particularly through strengthening the school’s vision and mission, improving teacher competencies, optimizing resource management, and fostering active stakeholder participation. Moreover, visionary leadership, a strong quality culture, and supportive school environments are identified as key determinants of successful strategy implementation. This study concludes that strategic management is not merely an administrative tool but a transformative approach capable of guiding schools toward continuous quality improvement.